Pengaruh Senam Otak Terhadap Keseimbangan Dinamis Pada Anak Usia 7-8 Tahun Di Sd Negeri Pabelan 03 Mendungan Kartasura Sukoharjo - Nafarin, Muhammad Febry, Agus Widodo, S.Fis, M.Kes (2016)
Background: Playing football in addition requires good physical fitness, body balance is also very important, this is to reduce the risk of falling when running and dribbling. One effort to improve the dynamic balance is a brain gym exercises. Case in SD Negeri Pabelan 03 Mendungan Kartasura Sukoharjo in playing football suffered many falls during the game. Objective: To determine the effect of brain exercise influence on the dynamic balance in children aged 7-8 years. Methods: This study was conducted in October 2016. The research method using quasi-experimental approach with the design of two groups pre and post-test experimental design with control group design. The samples were 32 students in grade 2-3 age 7-8 years of elementary school children Pabelan 03 Mendungan Pabelan Kartasura Sukoharjo. The sampling technique used purposive sampling. The research instrument used brain exercises for 4 weeks with a frequency of exercise three times a week with each session for 15 minutes. Dynamic balance is measured using the Balance Beam Walking Test of bamboo sticks. Data analysis using the Wilcoxon test and Mann Whitney test. Result: Unknown pre-test treatment group much in the dynamic balance enough categories, and post-test many in both categories. The control group pre-test and post-test many in the poor category. Wilcoxon test results the group treated with p = 0.001. The control group with p = 0.140. The result of the influence of different test with Mann Whitney test obtained by value p = 0.001 Conclusion: There is a brain exercise influence on the dynamic balance in children aged 7-8 years.